PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, UMUR PERUSAHAAN DAN LIKUIDITAS TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI 2016-2018 - Raja Ade Fitrasari Mochtar (UIR Press, 2022)
This research was conducted to analyze the effect Profitability, Leverage, Company Size, Company Age, and Liquidity On Timeliness of Financial Report Submission conducted in mining companies listed on May 2016-2018. The population in this study were 47 manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2018. Samples were selected using the purposive sampling method. Based on the purposive sampling method, the samples obtained were 33 companies for 3 years so that there were 99 companies. Data analyzed using multiple regression analysis using SPPS version 25. Based on the test results of this study, a logistics regression test (parcial test) showed that Age (Sig 0,077) and Liqiudity (Sig 0,731) had no effect on Timeliness of Financial Report Submission. This is indicated in the test results that the significance value of the variable is greater than (>) 0.05 and the Tcount value is smaller than the value of Ttable. While Profitability (Sig 0.013), Leverage (Sig 0.026) and Company Size (Sig 0.007) affect Timeliness of Financial Report Submission.This is indicated in the test results that the significance value of the variable is smaller than (<) 0.05 and the value of T is greater than the value of the table. Keywords:Profitability, Leverage, Company Size, Company Age, Liquidityand Timeliness of Financial Report Submission